Adverse Drug Reactions to Antituberculosis Drugs in Tuberculosis Patients Using the Naranjo Algorithm at a Regional Hospital in Mataram - Recta Olivia Umboro; Fitri Apriliany; Pande Made Desy Ratnasari; Anita Mursiany (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Tuberculosis (TB) remains one of the major health problems in Indonesia. As of October 2023, 67,770 TB cases were reported in West Nusa Tenggara Province (NTB). TB treatment requires long-term therapy using combinations of antituberculosis drugs (ATBD), which have the potential to cause Adverse Drug Reactions (ADRs). ADRs that are not properly identified and managed can increase morbidity and mortality in TB patients and negatively affect treatment outcomes.This study aimed to determine the incidence of ADRs related to the use of ATBD in TB patients at Mataram City Regional General Hospital, NTB, from February to June 2023. This observational study employed a cross-sectional design. Data were collected through structured interviews, and the Naranjo Algorithm was used to assess the causality between reported symptoms and drug use. A total of 66 patients were included in the study. The most common definite ADRs was associated with rifampicin, characterized by reddish discoloration of urine (45.70%), followed by isoniazid-induced fatigue (34%). Probable ADRs were observed with streptomycin, isoniazid, rifampicin, and pyrazinamide, mainly presenting as itching or skin rash (11.10%). Possible ADRs included headache (4.90%) and pain (4.30%), predominantly related to rifampicin use. In conclusion, ADRs among TB patients receiving ATBD at Mataram City Regional General Hospital were diverse, with rifampicin-related urine discoloration being the most prevalent. Identification of ADRs using the Naranjo Algorithm is important for early intervention, improving treatment success, and preventing drug resistance.